A critical analysis of the implications of commissioner South African Revenue Service v Brummeria Renaissance (Pty) Ltd on the taxation of the benefits of interest-free shareholders' loans - Cronje, M. (University of Pretoria, 2013)
Dissertation (MCom)--University of Pretoria, 2009.